A Bi-Dimensional Taxonomy of Social Responsivity in Middle Childhood: Prosociality and Reactive Aggression Predict Externalizing Behavior Over Time - Dobbelaar, Simone; van Duijvenvoorde, Anna C. K.; Achterberg, Michelle; van der Meulen, Mara; Crone, Eveline A. (Frontiers in Psychology, 2021)
Developing social skills is essential to succeed in social relations. Two important social constructs in middle childhood, prosocial behavior and reactive aggression, are often regarded as separate behaviors with opposing developmental outcomes. However, there is increasing evidence for the co-occurrence of prosociality and aggression, as both might indicate responsivity to the social environment. Here, we tested whether a bi-dimensional taxonomy of prosociality and reactive aggression could predict internalizing and externalizing problems over time. We re-analyzed data of two well-validated experimental tasks for prosociality (the Prosocial Cyberball Game) and reactive aggression (the Social Network Aggression Task) in a developmental population sample (n = 496, 7-9 years old). Results revealed no associations between prosociality and reactive aggression, confirming the independence of those constructs. Interestingly, although prosociality and reactive aggression independently did not predict problem behavior, the interaction of both was negatively predictive of changes in externalizing problems over time. Specifically, only children who scored low on both prosociality and reactive aggression showed an increase in externalizing problems one year later, whereas levels of externalizing problems did not change for children who scored high on both types of behavior. Thus, our results suggest that at an individual level, reactive aggression in middle childhood might not always be maladaptive when combined with prosocial behavior, thereby confirming the importance of studying social competence across multiple dimensions.